Willingness of Generation Z towards financial planning - Yee, Wil Shen; Soo, Jin Shen; Lim, Tiong Wei; Lee, Jin Sheng (2024)
Although Generation Z has never had more access to financial information due to digital transformation, most of them are unable to handle even the most fundamental aspects of money management. The current study looks at four key factors—financial knowledge, financial attitude, financial behavior, and financial literacy to determine the willingness of Generation Z towards financial planning. Questionnaires were sent to 385 members of the Malaysian Gen-Z population, chosen using probability sampling, to gather data for this research. Afterwards, it was determined by multiple linear regression analysis that the willingness of generation Z towards financial planning is significantly influenced by financial knowledge, financial attitude, financial behavior and financial literacy. The final section offers suggestions for creating financial education initiatives that specifically address the needs of Generation Z to raise their level of financial knowledge, financial behavior, financial attitude and financial literacy. In doing so, the study continues to add to the body of knowledge regarding financial planning while also strengthening the case for developing a generation that is more robust and more financially prepared.